2021
DOI: 10.1155/2021/9944132
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of NOLC1 Inhibits PI3K-AKT Pathway to Improve the Poor Prognosis of Esophageal Carcinoma

Abstract: Objective. Esophageal carcinoma (ESCA) is a common malignant gastrointestinal tumor. The abnormal expression of NOLC1 is involved in the tumorigenesis of various human tumors, whereas the function and mechanism of NOLC1 in ESCA remain unclear. In this study, we explored the relationship between NOLC1 and poor prognosis of ESCA, and its role and mechanism in the occurrence of ESCA. Methods. The NOLC1 expression in ESCA tissues and cell lines was determined by qRT-PCR, immunohistochemistry, or western blot. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Fuwen Yuan et al also found that highly expressed NOLC1 promotes cell senescence and inhibits cell proliferation in HCC and plays a certain role in cell senescence through the CSIG–NOLC1–RRNA pathway (Yuan et al 2017 ). Kong et al ( 2021 ) also reported that NOLC1 over-expression is considered to be an independent adverse factor affecting the overall survival of esophageal cancer patients and can participate in the invasion and protein expression of esophageal cancer through the PI3K/AKT pathway. However, the significance of NOLC1 expression in the prognosis of colorectal cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Fuwen Yuan et al also found that highly expressed NOLC1 promotes cell senescence and inhibits cell proliferation in HCC and plays a certain role in cell senescence through the CSIG–NOLC1–RRNA pathway (Yuan et al 2017 ). Kong et al ( 2021 ) also reported that NOLC1 over-expression is considered to be an independent adverse factor affecting the overall survival of esophageal cancer patients and can participate in the invasion and protein expression of esophageal cancer through the PI3K/AKT pathway. However, the significance of NOLC1 expression in the prognosis of colorectal cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out by Kong et al [ 47 ], the role of NOLC1 in esophageal cancer (ESCA) was determined, and its gene expression in ESCA tissues and cell lines was evaluated by qRT-PCR, immunohistochemistry or Western blotting. Among the results, overexpression of NOLC1 was observed in ESCA tissues and ESCA cell lines (EC9706, Eca109, TE-13, Kyse170, T.TN) compared to adjacent normal tissues and normal esophageal cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…So, NOLC1 overexpression was also associated with reduced overall survival rates for patients with ESCA. NOLC1 knockdown, in turn, inhibited proliferation, migration, invasion and cyclin B1 expression and promoted apoptosis and cleaved-caspase-3 expression of two ESCA cell lines [ 47 ]. The in-depth study of data on NOLC1 gene expression and its role in carcinogenesis shows that the protein encoded by this gene is a promising therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also promotes the proliferation and malignant transformation of tumor cells through phosphorylation of PI3K and AKT protein and inhibits the apoptosis of tumor cells. More and more studies have reported that PI3K/AKT signaling pathway regulates the growth, apoptosis and invasion of tumor cells in malignant tumors of digestive system [27] .Previous studies p-PI3K can activate Akt to form p-Akt, and then participate in the process of gastric cancer development and development [28,29,30,31,32] .ZHANG et al [33] validated that YARS exerted its malignant roles in GC through activated PI3K-Akt signaling.KONG et al's [34] experiments showed that NOLC1 overexpression accelerated proliferation, migration, invasion, and cyclin B1 expression and inhibited the apoptosis and cleaved-caspase-3 expression of Esophageal carcinoma (ESCA) cells via activating PI3K/AKT pathway. CHENG et al [35] found blockage of Osteopontin (OPN) downregulates the activation of the PI3K-AKT-GSK/3b-b/catenin pathway, accompanied by the inhibition of CRC stem cell proportion.…”
Section: Discussionmentioning
confidence: 99%